Pengaruh Kecerdasan IQ, EQ dan SQ Personel Intelijen terhadap Kemampuan Analisis di Koarmada II - Nugraha, Rio Aditya; Widayat, Wahyu Agus; Pandjaitan, Manahan Budiarto (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2024)
The research aims to find out the impact of IQ, EQ, and SQ intelligence on the capabilities of intelligence personnel in Koarmada II. The research method uses quantitative methods. The population in this study refers to the total Koarmada II Intelligence Satker personnel in real terms based on the Intelligence Personnel List (DSP) of Koarmada II, consisting of Satker Sintel, Denintel, and Satpam Denma, for a total of 72 personnel. The primary data in this study used a questionnaire with a Likert scale. Data analysis techniques use descriptive statistics and inferential statistics. The results of the research showed that IQ had a positive and significant influence on the analytical capabilities of Koarmada II by 24.3%. EQ intelligence had a significant and positive impact on analytical abilities in Koarmada 2 by 29.8%. SQ intelligence had a negative and significant impact on the analysis capability in Koarma II by 23.8%. IQ intelligence, EQ intelligence, and SQ intelligence, combined, had a good and significant effect on analysis capacities in Koarmada 2, by 43.4%, and the remaining 56.6% were influenced by other variables that were not studied.